Phenomenon of Demikhov. In the Vishnevsky Institute of Surgery (1947–1955): Scientifi c session at the Institute of Surgery (presentation by G.A. Rikhter, debate, conclusions) - S. P. Glyantsev (Трансплантология (Москва))
.